Echocardiographic assessment of right ventricular systolic function - Wu, Victor Chien-Chia (Cardiovasc Diagn Ther, 2018)
Assessment of right chamber function has become increasingly popular and important in recent decades, complementing the evaluation of left chamber functional parameters. The late adoption and integration of right ventricular (RV) function into a complete evaluation of cardiac function could be due in part to the difficulty in visualization of the whole right ventricle, inconsistency in the analysis of RV parameters, and poor understanding of the impact of RV function on prognosis. From M-mode to 2-dimensional (2D) measurements of RV size and function, there have been arrays of parameters that provide important information of the right ventricle. However, there are limitations of using 2D echocardiography to quantify RV volume and ejection fraction (EF), and currently accurate measurements of RV volumes and EF can be obtained using cardiac magnetic resonance (CMR) imaging. Using 3-dimensional echocardiography (3DE), the measurements of RV volumes and EF have become feasible and reproducible. Importantly, 3D measurements have been validated against CMR with higher correlation compared to 2D measurements. With the establishment of reference values, 3D echocardiography determined RV volumes and EF have the potential for better understanding of RV function and exploration of its significance for outcome research in various clinical scenarios.